Review of the 1977 Decision on Surveillance over Exchange Rate Policies : Proposal for a New Decision. (Policy Papers; Policy Paper ;, 2007)
This paper presents a draft Decision that reflects the guidance provided by the Board. In February, the Board endorsed three overarching principles to guide a new Decision: (i) no new obligations for members, together with confirmation that dialogue and persuasion are key pillars of surveillance; (ii) due regard for country circumstances and emphasis on the need for evenhandedness; and (iii) continued flexibility.